2015
DOI: 10.1103/physreve.92.042156
|View full text |Cite
|
Sign up to set email alerts
|

Lévy flights with power-law absorption

Abstract: We consider a particle performing a stochastic motion on a one-dimension lattice with jump lengths distributed according to a power-law with exponent µ + 1. Assuming that the walker moves in the presence of a distribution a(x) of targets (traps) depending on the spatial coordinate x, we study the probability that the walker will eventually find any target (will eventually be trapped). We focus on the case of power-law distributions a(x) ∼ x −α and we find that, as long as µ < α, there is a finite probability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…the target is discovered with a power-law decaying probabilityin Ref. [63]. In that case, if the stable index α < 1, the search still can be absolutely reliable (P = 1), if the scaling exponent characterising an absorption probability β ≤ α, i.e., the target localisation or absorption probability is delocalised stronger than the LF process.…”
Section: Discussionmentioning
confidence: 99%
“…the target is discovered with a power-law decaying probabilityin Ref. [63]. In that case, if the stable index α < 1, the search still can be absolutely reliable (P = 1), if the scaling exponent characterising an absorption probability β ≤ α, i.e., the target localisation or absorption probability is delocalised stronger than the LF process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the probability of encounter along a tooth remains a(Y ) ∼ 1/Y , consequently also in these cases the two-particle transience is ensured (see Sec. II and the condition of the paper [32]) as proven in [15,23].…”
Section: Two Random Walkers On Bundled Structuresmentioning
confidence: 89%
“…This model was studied in detail in [32], where it is shown that the Lévy flight characterized by a jump distribution h(ξ) ∼ ξ −µ−1 in the presence of traps with distribution scaling as a(ξ) ∼ ξ −α has a finite probability of never being absorbed when the displacement exponent µ (in our case µ = 1/2) is lower than the absorption exponent α (in our case α = 1). Since here this condition is fulfilled, we recover the two-particle transience on combs, that is, the two particles have a finite probability of never meeting, regardless of their starting position.…”
Section: Two Random Walkers On Combsmentioning
confidence: 93%
See 2 more Smart Citations